Permanent academic update of the teacher: Challenge in the face of the liberalization of knowledge and technological advance - Palma-González, Felipe Rubén; Borrego-Rosas, Carlos Esteban; Rodriguez-Barboza, Jhonny Richard; Marquez-Yauri, Heyner Yuliano (Revista de Ciencias Sociales, 2024)
The objective of this article is to reflect -through hermeneutic documentary analysis- on permanent and continuous academic teacher training with a view to generating emotional-affective and technological competences to face the different and accelerated changes in current social relations. The didactic-pedagogical work of educators is complex, diverse, adaptive, and challenging; It requires the instrumentalization of affective relationships with students and stakeholders, since the liberalization of scientific knowledge has brought with it the unequivocal use of it, due to the consequent loss of values and professional ethics. Besises, the accelerated growth of emerging communication technologies and scientific applications, their ignorance has delayed the pedagogical work, outdated it, even sometimes surpassed by students. Therefore, teacher training programs must be able to generate in teachers’ emotional competencies and creation of skills for the pedagogical management of emerging technologies. In conclusion, this purpose implies overcoming traditional training plans and going towards reforms and implementation of lifelong learning programs, supported by institutional policy and the high commitment of strategic levels, to contribute to educational quality.